Systemic lupus erythematosus as a multidisciplinary problem (clinical case) - Talash, V.V.; Katerenchuk, I.P.; Kostrikova, Yu.A.; Yarmola, T.I.; Hutsalenko, O.O.; Pustovoyt, Н.L.; Tkachenko, L.A.; Mokhnachev, O.V.; Rustamian, S.T.; Talash, V.V.; Sarychev, L.P.; Savchenko, R.B. (Medicni Perspektivi, 2025)
Systemic lupus erythematosus (SLE) is a prognostically unfavorable systemic connective tissue disease with heterogeneous clinical manifestations, development of complications, and an unpredictable wave-like course, which complicates the diagnosis of this pathology. The relevance of this clinical case is determined by a number of features: the debut of SLE with isolated kidney damage, an 11-year delay in the date of diagnosis, and the occurrence of an extremely rare complication – lupus crisis (LC), which became fatal for the patient. The aim of the work: to analyze a clinical case as unique in terms of the features of the debut and clinical course of systemic lupus erythematosus, which has become a multidisciplinary problem, to highlight the reasons for the delay in diagnosis verification, to assess, in dynamics, the effectiveness of the prescribed treatment and to report on the development of a multiorgan lupus crisis. The article analyzes data from the medical documents of a 31-year-old inpatient. An illustrative clinical case of SLE, which debuted with glomerulonephritis at the age of 16, 11 years before the appearance of specific clinical symptoms that met the criteria of the American College of Rheumatology and the European League Against Rheumatism 2019, is presented. The level of immunological indicators specific for SLE – antinuclear antibodies to double-stranded deoxyribonucleic acid increased in the patient in 2023, i.e. 4 years later. The patient’s refusal of nephro biopsy, starting from the debut of the disease and from pathogenetic therapy at the stage of diagnosis and during the next 4 years. led to increased SLE activity, frequent relapses with the development of polymorbid pathology and, incompatible with life, multiorgan lupus crisis. The article describes in detail the dynamics of clinical manifestations of SLE and LC. The stages of diagnostic search, features of differential diagnosis and treatment of SLE and LC are discussed on the example of a clinical case. Based on the results of a review of the medical literature, analysis of articles, databases PubMed, SCOPUS, Web of Science, MedScape, the current state of the problem is highlighted, literature data on the incidence, features of the clinical course, diagnosis and treatment of SLE, its complications are summarized. The description of the clinical case, analysis of the literature is an addition to modern information about the possible clinical manifestations and consequences of SLE with the development of a severe, extremely rare complication – lupus crisis.